PATH-05 Challenge and clinical relevance of a non-matching classifier output in genome-wide DNA methylation analysis for CNS neoplasms in pediatric and adolescent patients. (3rd June 2022) - Drexler, Richard; Eckhardt, Alicia; Bode, Helena; Lamszus, Katrin; Westphal, Manfred; Schüller, Ulrich; Mohme, Malte
Abstract: OBJECTIVE : The molecular classification of CNS tumors has revolutionized our understanding of the biological heterogeneity and diversity of tumor subtypes. DNA methylation-based classification allows to discriminate subtypes. Although DNA methylation-based classification can diagnose tumors with high specificity, there are tumors which cannot be classified. We aimed to gain further insight into these challenging cases. METHODS : Overall, 21 patients with a CNS tumor that was non-classifiable (confidence score <0.3), or had a low confidence score (<0.9) using the DNA methylation-based classifier version 11b4, were included. Tumors were re-classified using version (v12.3), and clinical data were analyzed. RESULTS : A total of 21 pediatric and adolescent brain tumors with a calibrated score below 0.9 in the classifier output were identified. Of these, 11 patients (52.4 %) were assigned to the "no matching methylation class" with a score below 0.3. IDH-wild type glioblastoma (23.8 %), ETMR (14.3 %), and DMG (14.3 %) were the most common histological diagnoses. Surgical and clinicopathological features as well as DNA input and tumor purity did not influence the confidence score. Cases with non-classifiable tumors had a significantly longer time until a decision for adjuvant therapy (p<0.01). Application of the latest classifier version v12.3 led to a re-classification of 9 (42.9 %) cases, of which 5 cases (55.6 %) had an improved calibrated score. CONCLUSION : Our study presents unclassifiable cases and the possible clinical impact when waiting for the accurate diagnosis in these challenging cases. Even though DNA methylation profiling significantly contributes to advanced CNS tumor diagnostics, clinicians should be aware of a prolonged interval to treatment initiation, especially for highly malignant brain tumors. Therefore, we would recommend to schedule adjuvant treatment as early as possible, if surgical and histological results are suspicious for this disease.